2019
DOI: 10.1186/s12903-019-0865-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of universal adhesives on microtensile bond strength to hybrid ceramic

Abstract: Background The aim of this study was to evaluate the effect of universal adhesives (UA) and silane on the microtensile bond strength (μTBS) of resin cement to a hybrid ceramic Vita Enamic (VE). Methods VE specimens were acid etched using hydrofluoric acid (HF) and were assigned to three groups ( n = 10) based on the applied bonding technique. In group 1 (S), a silane-based primer was used as a surface treatment prior to the application of a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
(32 reference statements)
0
21
0
1
Order By: Relevance
“…31 Earlier researchers have reported that the thermocycling decreased bond strength of PIC to the resin luting agent. 32 The reduced failure load in the radicular extension group could be due to the combined effect of increased stress concentration and reduced bond strength. Hence most failures in this group were favorable with the debonding of endocrowns.…”
Section: Discussionmentioning
confidence: 97%
“…31 Earlier researchers have reported that the thermocycling decreased bond strength of PIC to the resin luting agent. 32 The reduced failure load in the radicular extension group could be due to the combined effect of increased stress concentration and reduced bond strength. Hence most failures in this group were favorable with the debonding of endocrowns.…”
Section: Discussionmentioning
confidence: 97%
“…Silane application has been recommended as a chemical pretreatment for DF-RCBs 23,35) as well as for PICN-RCBs 11,29,30,41) . Trialkoxysilanes are bi-functional molecules whose alkoxy groups have the ability to condensate with hydroxyl (-OH) groups on the substrate surface while their carbon double bonds can polymerize with the resin monomers by photo-initiated free radical polymerization 42,43) .…”
Section: Discussionmentioning
confidence: 99%
“…In evaluating the bond strength of PICN with two types of resin cement after several acid etching protocols combined with silane, Single Bond Universal and an association of both primers, Rohr et al 22 (2017) found that the highest bond strengths values were achieved when silane was applied followed by the universal adhesive after 5% hydrofluoric acid conditioning for 30 to 60 s. Corroborating the findings of the present study, the authors also did not find adequate mean bond strength values when universal adhesive was applied solely after HF 22 . Furthermore, Awad et al 19 (2019) also found a significantly higher performance of silane group and low bond strengths of universal adhesives after aging in comparing the behavior of a silane primer, a silane-containing universal adhesive and a silane-free universal adhesive after HF etching (4.6%) on μTBS of PICN with resin cement. These results seem to demonstrate that chemical adhesion promoted by UA and PICN was not sufficient compared to silane (HF-S).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, adhesive bonding is related to a higher fracture strength of indirect restorations and restored teeth 4,9,10 . Methods which increase the surface properties would be clinically advantageous in order to improve the adhesive bond to ceramic surfaces 7,[11][12][13] , promoting micromechanical interlocking [14][15][16] and/or surface reactivity for chemical bonding [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation